Rancang Bangun Sasaran Tembak Berbasis Mikrokontroler - Sufandi, Muhammad Ridhwan; Rahayu, Wiwit Indah; widi kurniawan, adrik (Electrical Network Systems and Sources, 2024)
Members of the Indonesian National Armed Forces (TNI) are required to master shooting skills through regular practice. However, the efficiency of shooting training is often hampered by the absence of an automatic target scoring system. To address this issue, a device in the shape of a square with dimensions of 50x50 cm was developed, equipped with laser sensors on the x and y axes. This device can automatically detect and calculate scores when a bullet hits the target accurately, with the results displayed on a P10 monitor. This tool aims to enhance the efficiency and accuracy of shooting training for TNI members.